A revision of the Upper Cretaceous shark Ptychodus mediterraneus Canavari, 1916 from northeastern Italy, with a reassessment of P. latissimus and P. polygyrus Agassiz, 1835 (Chondrichthyes; Elasmobranchii). (June 2020) - Amadori, Manuel; Amalfitano, Jacopo; Giusberti, Luca; Fornaciari, Eliana; Carnevale, Giorgio; Kriwet, Jürgen
Abstract: Dental and skeletal remains of Ptychodus mediterraneus from the Upper Cretaceous Scaglia Rossa Formation of northeastern Italy are described and discussed herein, together with isolated teeth of P. latissimus and P. polygyrus from the English Chalk of Sussex, southern England. The redescription of the holotype of Ptychodus mediterraneus and lectotype fixations for P. latissimus and P. polygyrus allow the systematic reassessment of the three low-crowned Ptychodus species. In addition, these taxa are compared with other morphologically similar species, such as P. martini and P. marginalis . Micropalaeontological analyses suggest a Turonian age for the low-crowned P. mediterraneus . Based on articulated tooth sets of P. mediterraneus, the pavement-like dentitions of this durophagous taxon are reconstructed herein, revealing a marked dignathic heterodonty. Imbricated dentitions observed in articulated specimens of Ptychodus mediterraneus also suggest broad distributions of bite-induced load on tooth plates; the dental features of this low-crowned durophagous shark indicate a high specialization for grinding thick-shelled bivalves (e.g., inoceramids and rudists). Fragments of cranial mineralized cartilages (e.g., a 'V-shaped' jaw portion) of P. mediterraneus are consistent to those commonly occurring in fusiform sharks. Evidences of scavenging on Ptychodus recorded on cartilages and tooth-bioerosion are also reported herein. Moreover, a posterior-to-anterior tooth replacement is hypothesized for Ptychodus based on the abrasion patterns observed in articulated dental sets. New insights on the palaeoecology and palaeobiology of Ptychodus are also provided. Highlights: Systematic reassessment of Ptychodus latissimus, P. polygyrus and P. mediterraneus. Detailed description of the anatomy of P. mediterraneus. Reconstruction of dental plates of P. mediterraneus based on articulated specimens. Discussion about feeding specialization, tooth replacement and body morphology. Taphonomic remarks focused on decay of carcass, scavenging and microborings.